Thigh and psoas major muscularity and its relation to running mechanics in sprinters - Ema, R.; Sakaguchi, M.; Kawakami, Y. (Medicine & Science in Sports & Exercise, 2018)
Purpose We aimed to examine the morphological characteristics of the thigh and psoas major muscles in sprinters as well as interrelations among their muscularity, hip joint mechanics, and running speed during maximal running.